PENERAPAN 7 PILAR KOMUNIKASI BISNIS PRODUK BARENBLISS DI INDONESIA - Salman, Rifa Syakira; Barkah, Cecep Safaatul; Auliana, Lina; Sukoco, Iwan (Jurnal Ekonomi Manajemen, 2022)
The presence of Barenbliss in Indonesia was accompanied by the increasing popularity of K-beauty which became the K-wave phenomenon, this is also influenced by the existence of K-pop and K-drama which are favorites by most Indonesian people. So Barenbliss products gained popularity in a short time. The recognition of Barenbliss among people who love beauty products cannot be separated from the business communication strategy used by the company.The focus of this research is to reveal how the 7 pillars of business communication strategies are used by Barenbliss to increase brand awarenes. Qualitative research method is the method used in this study, and observation is the data collection technique used in the study. The results of this study are that Barenbliss has carried out a business communication strategy well, it can be seen from the speed with which products gain popularity and some products become favorite products on one of the largest online shopping platforms in Indonesia, and also become the choice of several women based on beautynesian data, but BNB products still require publications to reach all levels of society, especially women.Â